Farmacocinética pré-clínica e avaliação toxicológica do novo composto α2-adrenérgico 3-(2-cloro-6-fluorobenzil)-imidazolidina-2,4-diona - PT-31 GIRSUPAN - Cimatti, Helen Mariana Baldan [UNESP] (2013)
The compound 3-(2-chloro-6-fluoro-benzyl)-imidazolidine-2,4-dione - GIRSUPAN PT-31 was designed by the research group of the Federal University of Pernambuco. The PT-31 GIRSUPAN has analgesic effect from the activation of 2-adrenoceptor in central nervous system. Still, when administered by intraperitoneal (ip) route in mice (15 mg/kg), the compound has synergistic effect with morphine. The aim of this study was to investigate the physicochemical properties, toxicity aspects and pharmacokinetic profile of the compound PT-31 GIRSUPAN with potential application in the treatment of pain. The tests for the compound were: determination of the partition coefficient (logP); study chemical stability in vitro (buffer) and ex vivo (rat plasma); evaluation of pharmacokinetic profile in Wistar rats after intraperitoneal and oral administrations in a single dose. The PT-31 GIRSUPAN was administered alone and in association with morphine to assessment of liver and kidney toxicity in Wistar rats, and to assessment of the potential for addiction. Moreover, to achieve the pharmacokinetic and stability studies were developed and validated HPLC methods with UV and mass detection, for the determination of PT-31 GIRSUPAN in solution and rat plasma. The logP of PT-31 GIRSUPAN was 1.6 ± 0.1 by in silico method and 1.2 ± 0.1 by shake flask method. The analytical and bioanalytical methods developed showed confidence limits appropriate for the intended purpose and the results of chemical stability and ex vivo demonstrated that the compound was stable in the evaluated pHs (3.0 and 7.4) and in the rat plasma, both by 12 hours. In pharmacokinetic analysis of the compound administered alone was observed clearance (Cl) similar between ip and oral routes, however the volume of distribution (0.978 and 0.681 L/kg) and elimination half-life (3.7 and 2.9 h) were significantly higher in oral administration (p<0,05). The association of the compound with morphine ...